RESEARCH OF THE EFFECTIVENESS OF THE USE OF THE VIDEO ASSISTANT REFEREE IN FUTSAL - Панчук, Тарас; Ільїн, Володимир; Криштопа, Людмила; Чайковський, Ілля; Шекета, Василь (SWorldJournal, 2025)
The paper presents research on the effectiveness of using the video assistant referee system to increase the accuracy of decision-making during futsal matches. The authors obtained new results, and it was established that the correctness of decision-makin